GENERATIVE AI FOR JUST-IN-TIME MINDFULNESS CONTENT - Boloban, Oleh (Sworld-Us Conference proceedings, 2025)
The paper describes a framework for Just-in-Time Mindfulness that combines data from everyday wearables with generative artificial intelligence to offer the user a short, personalized mindfulness practice at the exact moment when the risk of stress increa